The Impact of Knowledge Management Processes on Operational Performance as Mediated by IT Agility - Al-Qatawneh, Nancy Abdal Wahab; Al-Tarawneh, Samiah Jaber; Al-Qatawneh, Nour Abdel Wahab; Al-Adaileh, Raid Mohd (International Review of Management and Marketing, 2019)
In this study the main goal is to investigate the impact of knowledge management processes (KMPs) on operational performance (OP) as mediated by IT agility (ITA). The data were collected using a questionnaire, as the instrument for the primary data collection, with total collected back responses of 314 from university lecturers and employees have actually participated. Partial least squares regression modeling technique was used to fully analyze the data in order to determine what level of the relationship between KMPs and OP as mediated by IT agility existed. The main findings were related to confirming the four main hypotheses of the research that were related to testing if there were relationships between the KMPs (represented by four surrogate measures, namely, knowledge creation, knowledge storage, knowledge sharing and knowledge application) and OP, as well as if the KMPs was related to the OP as mediated by IT agility. Keywords: Knowledge Management, Mu’tah University, Operational Performance, Technology, IT Agility, Partial Least Squares Analysis JEL Classifications: D83, M1 DOI: https://doi.org/10.32479/irmm.7191